Peran teknologi terhadap lingkungan dan pembangunan di pedesaan - Iqbal, Muhammad (Maliki Interdisciplinary Journal, 2025)
This article explores the role of green technology in advancing sustainable development in rural areas, with a case study on the Subak irrigation system in Tabanan, Bali. Green technology is defined as an innovation that promotes energy efficiency, environmental preservation, and community empowerment. Findings show that the implementation of solar-powered irrigation pumps in Subak reduces both emissions and operational costs while strengthening the local socio-ecological system. The article highlights the successful integration of traditional wisdom and modern technology, while also addressing structural challenges such as funding, institutional capacity, and cultural resistance. Through a reflective, data-informed approach, this article offers recommendations for government, academia, rural communities, and journal platforms to promote green technology adoption in a context-sensitive manner. The study concludes that green tech in rural areas is not only technically feasible but also strategically valuable for building independent, resilient, and ecologically aware villages.